Neoplastic diseases of fish : Review - Márton, Hoitsy; Gál, János; Baksa, Ferenc; Molnár, Tamás Gergely (Acta Agraria Kaposváriensis, 2022)
Neoplastic diseases of fishes are an important topic in the aquatic veterinarian field. The neoplastic malformations are affected the fish species from the early stage of evolution. Nowadays the aquaculture industry is one of the most important food sources. The healthcare of the animals is of great importance in fish farms. Especially the brood stocks have a significant value on the farms, therefore the prevention of illnesses is crucial. The koi and other pet fish could also have tumours. The animals of the hobby keepers are also valuable. The neoplasms can develop from any organ in the fish. The investigation of tumours growing in fish is considered an important field of both human and veterinary research also.
Keywords: fish; tumour; diseases; neoplasia